Անձավի ուրարտական վահանի առյուծների զույգը - Սարգիս Պետրոսյան (ՀՀ ԳԱԱ հրատ.)
При раскопках крепости Андзав (нынешн. Анзаф в районе города Вана) был обнаружен обломок урартского щита, украшенный изображениями урартских богов и фантастических существ. Из последних пара львов изображена перед лучезарным богом Солнца. Они нападали на конников вражеской армии. В гомеровском описании щита Агамемнона (“Илиада”, XI, 31-36) упоминаются Деймо и Фобос (Страх и Ужас, Страх и Трепет), которые в древнегреческой мифологии выступают как слуги и возницы бога войны Ареса. The author of the article holds the view that the pair of personified Fears in the traditions of ancient Greeks and Hittites as well as Armenians was preceded by the archaic zoomorphic pair assuming the appearance of winged lions. It were exactly these lions pictured before the radiant God of the Sun on a piece of Urartian shield from Andzav (a fortress near Van). In ancient Greek mythology they were personified by Deimos and Phobos (Fear and Horror), i.e. the servants and drivers of Ares, the God of War.
Keywords: History; D History; G Geography; Anthropology; Recreation; GR Folklore